Peningkatan Kualitas Pengajaran Matematika Pada Tingkat Pendidikan Menengah - H. Djaali (Universitas Negeri Malang, 2016)
The achievements in the studies of mathematics at the junior and senior secondary schools in Ujung Pandang is quite low. It seems that the teaching of mathematics at those schools do not meet the requirement of proper mathematics teaching. Not only the students do not sufficiently master the prerequisite of learning later topics in mathematics, the teaching competencies of mathematics teachers are also quite insufficient. Learning school mathematics should meet the requirement of learning hierarchies, while researches in the teaching of mathematics are important in improving the methods of the teaching of school mathematics.